The ecology of the invertebrate community of Borough Fen Decoy pond - Palmer, Margaret (Wildfowl, 1974)
The invertebrate fauna of the pond, which has existed for over 300 years, is listed. The ecological requirements of the different species are described, and the ways in which they are adapted to the particular conditions of Borough Fen discussed.